Are emergency physicians satisfied? An analysis of operational/organization factors. Issue 6 (21st December 2021) - Lall, Michelle D.; Chang, Bernard P.; Park, Joel; Tabatabai, Ramin R.; Manfredi, Rita A.; Baren, Jill M.; Castillo, Jenny
Abstract: Objective: Professional satisfaction is associated with career longevity, individual well‐being, and patient care and safety. Lack of physician engagement promotes the opposite. This study sought to identify important facets contributing to decreased career satisfaction using a large national data set of practicing emergency physicians. Methods: We performed a secondary analysis of the national Longitudinal Study of Emergency Physicians survey conducted by the American Board of Emergency Medicine. The survey was composed of 57 variables including career satisfaction as well as occupational and psychological variables potentially associated with career satisfaction. Factor analysis was used to determine the important latent variables. Ordinal logistic regression was performed to determine statistical significance among the latent variables with overall career satisfaction. Results: A total of 863 participants were recorded. The overall mean career satisfaction rate was 3.9 on a 5‐point Likert scale with 1 and 5 indicating "least satisfied" and "most satisfied, " respectively. Our analysis revealed 9 factors related to job satisfaction. Two latent factors, exhaustion/stress and administration/respect, were statistically significant. When comparing satisfaction scores between sex, there was a statistically significant difference with men reporting a higher satisfaction rate ( P = 0.0092). Age was also statistically significant with overall satisfaction lower for younger physicians than older physicians. Conclusion: Our study found that emergency physicians are overall satisfied with emergency medicine, although with variability depending on sex and age. In addition, we characterized job satisfaction into 9 factors that significantly contribute to job satisfaction. Future work exploring these factors may help elucidate the development of targeted interventions to improve professional well‐being in the emergency medicine workforce.